Shriram Transport Finance Company Ltd. : adoption of Fintech - Sahay, Arvind, (SAGE Business. Cases., 2019)
Shriram Transport Finance Company Ltd. (STFCL), the flagship company of the Shriram Group, India's largest player in commercial vehicle finance is trying to transition to a Fintech based model from a Relationship based model in order to provide its end consumers with speed, convenience, choice and savings, as digital transactions had reached an all-time high of 1.11 billion in January 2018 and digital payments were estimated to increase to USD 1 trillion by 2023.